2020
DOI: 10.3390/s20174890
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Review of the Algorithms for Removal of Electrocardiographic Interference from Trunk Electromyography

Abstract: Surface electromyogram (EMG) is a noninvasive measure of muscle electrical activity and has been widely used in a variety of applications. When recorded from the trunk, surface EMG can be contaminated by the cardiac electrical activity, i.e., the electrocardiogram (ECG). ECG may distort the desired EMG signal, complicating the extraction of reliable information from the trunk EMG. Several methods are available for ECG removal from the trunk EMG, but a comparative assessment of the performance of these methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The choice of the cut-off frequency should be carefully considered as a trade-off between EMG components to be maintained and ECG components to be eliminated. A cut-off frequency of 30 Hz is generally considered acceptable as suggested by Redfern et al [ 10 ] and recently confirmed by our previous study [ 11 ].…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…The choice of the cut-off frequency should be carefully considered as a trade-off between EMG components to be maintained and ECG components to be eliminated. A cut-off frequency of 30 Hz is generally considered acceptable as suggested by Redfern et al [ 10 ] and recently confirmed by our previous study [ 11 ].…”
Section: Introductionsupporting
confidence: 78%
“…TS produces significantly higher amplitude errors than SVD with all the tested signals, while in the frequency domain, it seems to be comparable to SVD only for an SNR = 20 dB. Previous results in the field already indicated this method as promising, identifying template subtraction as the most suitable for ECG denoising with respect to GT, HPF, wavelet transform, adaptive filtering, and ICA [ 11 ]. Nevertheless, the previous work did not consider different SNR condition of the signal in the analysis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Wavelet-based adaptive filters have been increasingly proposed for removal of ECG noise from EMG recordings of various muscles, including the diaphragm, and with and without the use of extra channels for ECG recording [15][16][17]20,29,30]. This method performs well particularly when the ECG to EMG amplitude is high.…”
Section: Comparison With a Wavelet-based Adaptive Filter And Simulated Emg Signalmentioning
confidence: 99%